Critical analysis of journal “Voprosy Kurortologii Fizioterpii i Lechbenoi Fizicheskoi Kultury” by the papers about peloids publisheds in the last 5 years - Graña, Narciso; Arranz, José Luís; García-Sánchez, Margarita; Párraga de las Marinas, Mª Elisa (Anales de Hidrología Médica, 2012)
In a recent publication in Medical Hidrology it drew our attention to the fact that, in MEDLINE data base, the scientific publication with more published articles about Medical Hidrology is the Russian journal “Voprosy Kurortologii, Fizioterapii i Lechbenoi Fizicheskoi Kultury”. It is for this reason that we recompilated the published articles about peloids in the last 5 years (2005-2010 period), with the objective to carry out a critical study of them, using a multifactor analysis of the scientific quality. We found 21 articles, and 10 of them achieve the selction criteria.